Therapeutic effect of cefozopran (SCE-2787), a new parenteral cephalosporin, against experimental infections in mice. - Iizawa, Y (1993)
The therapeutic effect of cefozopran (SCE-2787), a new semisynthetic parenteral cephalosporin, against experimental infections in mice was examined. Cefozopran was more effective than cefpiramide and was as effective as ceftazidime and cefpirome against acute respiratory tract infections caused by Klebsiella pneumoniae DT-S. In the model of chronic respiratory tract infection caused by K. pneumoniae 27, cefozopran was as effective as ceftazidime. The therapeutic effect of cefozopran against urinary tract infections caused by Pseudomonas aeruginosa P9 was superior to that of cefpirome and was equal to those of ceftazidime and cefclidin. In addition, cefozopran was more effective than ceftazidime and was as effective as flomoxef in a thigh muscle infection caused by methicillin-sensitive Staphylococcus aureus 308A-1. Against thigh muscle infections caused by methicillin-resistant S. aureus N133, cefozopran was the most effective agent. The potent therapeutic effect of cefozopran in those experimental infections in mice suggests that it would be effective against respiratory tract, urinary tract, and soft tissue infections caused by a variety of gram-positive and gram-negative bacteria in humans.